2011
DOI: 10.1097/mao.0b013e3182016534
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo and Clinical Test of Sensory Interaction and Balance in Ankylosing Spondylitis

Abstract: The present study shows an increased frequency of abnormal postural control in CTSIB test of vestibular origin in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Amor-Dorado et al. 87 found that the incidence of BPPV among 59 patients with ankylosing spondylitis was low (10%). Modugno et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amor-Dorado et al. 87 found that the incidence of BPPV among 59 patients with ankylosing spondylitis was low (10%). Modugno et al.…”
Section: Discussionmentioning
confidence: 99%
“…P erez et al 86 reported successful intratympanic methylprednisolone treatment in seven of nine patients with persistent posterior canal BPPV. Amor-Dorado et al 87 found that the incidence of BPPV among 59 patients with ankylosing spondylitis was low (10%). Modugno et al 88 found anti-thyroid antibodies in 27% of patients with BPPV and proposed the existence of immune complexmediated inner ear disease.…”
Section: Autoimmune Inflammatory or Rheumatologic Disordersmentioning
confidence: 99%
“…There are studies that reported increased frequency of vestibular pathologies in patients with AS, which may be due to an intra labyrinthical autoimmune process or ischemia [22]. In a study that evaluated patients with psoriatic arthritis, which is another typeof spondyloarthritis, the frequency of bilateral symmetrical hearing loss and abnormal vestibular test results were higher than in the control group [23].…”
Section: Vestibular Systemmentioning
confidence: 98%
“…Therefore, these studies confirm the presence of inner ear compromise and audiovestibular dysfunction in patients with AS that may be the result of vascular involvement or due to a direct immune-mediated injury of the inner ear and it could provide justification for rheumatologists or physicians to screen for inner ear compromise in their AS population. [51,52].…”
Section: Secondary Vasculitismentioning
confidence: 99%